Micro-solvation of tyrosine-kinase inhibitor AG1478 explored with fluorescence spectroscopy and computational chemistry. Issue 50 (21st June 2017) - Khattab, Muhammad; Wang, Feng; Clayton, Andrew H. A.
Abstract : Fluorescence quenching of the anticancer AG1478, by at least three explicit water molecules, can be exploited to probe drug–protein binding interactions. Abstract : Tyrosine kinase inhibitors (TKI) are an important class of molecules. Specific interactions of TKI with water are of interest since they appear in high resolution X-ray structures of TKI–protein complexes and are thought to be important determinants of drug efficacy. Methods for determining the specific interactions of TKI with water molecules in solution are therefore highly desirable. Recently, we revealed that the TKI, AG1478, exhibits absorbance and fluorescence spectra which are sensitive to the conformation of the molecule and the polarity of the surrounding environment. In the present work, we investigated the potential hydrogen bond binding sites of AG1478 using spectroscopic measurements of acetonitrile–water solutions. UV-Vis absorbance spectroscopy of AG1478 revealed H-bond interactions between water molecules and AG1478 in the ground state, as evidenced by changes in spectral shape and optical density with increases in water fraction. The fluorescence spectra of AG1478 in acetonitrile were also greatly influenced by water interactions, revealing fluorescence quenching (by 80%) with the addition of 2% by volume of water. The AG1478 fluorescence quantum yield decreased with increasing temperature in neat acetonitrile but revealed an unorthodox increase with increasing temperature in acetonitrile–water solution. Taken together, these changes are consistent with a specific complex or complexes formed between AG1478 and water molecules. Potential AG1478–water clusters were investigated using ab initio calculations. The effects of explicit hydrogen bonding on vertical excitation, topology and electronic configuration of AG1478 were examined computationally.